Economic trends and China's impact on world trade - Chris Nixon (New Zealand Institute of Economic Research (NZIER), 2005)
The Ministry of Economic Development has asked the NZIER to examine the impact of: [1] increased integration of the world economy i.e. the economic trends and how they impact on economic/business activity; and [2] China as a world economic power and how it is affecting globalisation trends. Are these trends accelerating and/or changing under China's influence? How important is China's influence compared with other influences? This paper is organised in a way that briefly canvasses each of the questions asked, explaining the context surrounding each question and providing indications as to where the answers may lie. In some instances, it is very uncertain as to how events may play out and this is signalled. We have focused on providing the reader with information from various sources on the big issues of global interconnectedness and Chinese integration into the world trading system that will stimulate debate rather than close it off.
Keywords: 330; Entwicklung; Wirtschaftswachstum; Weltwirtschaft; Welt; China